Evaluation of The Quality of Life After Surgical Extraction of Impacted Third Molars - Görkem Tekin; Nesrin Saruhan (Sakarya Tıp Dergisi, 2018)
Objective: The purpose of this study was to assess the quality of life of patients after the impacted third molar extraction with the OHIP-14 scale. Materials and Methods: A total of 100 patients with impacted third molars were included in this study. Patients' age, gender, position of third molar teeth and scores given to OHIP-14 scale were evaluated. Results: A total of 100 patients were included in this study, 64 of whom were female (64%) and 36 of whom were male (36%). The Simple Count values of the patients' responses to the OHIP-14 scale were found as minimum 0 maximum 44 (mean 11.64±9.8). When the responses' to the OHIP-14 scale were evaluated in terms of gender and Simple Count; count as minimum 0 maximum 44 (mean 11.83±9.8) in the female patients and minimum 0 maximum 36 (mean of 11.31±9.8) in the male patients and there was no statistically significant difference between male and female patients (p gt; 0.05). When the responses given to the questions on the OHIP-14 scale were evaluated as a total; it was seen that the patients describes most complaints with question 6, followed by 9, 4, 5, 8, 7, 3, 12, 1, 11, 2, 13, 14 and 10 questions respectively. Conclusion: It was seen that the patients were most uncomfortable with the 6th question and least comfortable with 10th question.